First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya - Tlili, Haithem; Abdellaoui, Khemais; Chouikha, Manel Ben; Mhafdhi, Mouna; Jemmazi, Adel; Ammar, Mohamed; Desutter-Grandcolas, Laure (Zootaxa, 2019)
The humpbacked grasshopper Dericorys albidula (Serville, 1838) (Orthoptera: Dericorythidae: Dericorythinae) is reported here for the first time from Southern Tunisia (Tozeur province) and northwestern Libya. Details on the ecological occurrence of D. albidula are given and compared to available data from Central Asia. A lectotype is designated for D. albidula and its type locality identified as the Sinaï desert in Egypt.